Characterization of aroma compounds in Portuguese extra virgin olive oils from Galega vulgar and Cobrançosa cultivars using GC-O and GC-x-GC-ToFMS - Peres, F. (2016)
Aroma compounds of virgin olive oils extracted from two olive cultivars – Galega Vulgar and Cobrançosa – grown in Beira Baixa region in central Portugalwere investigated. Gas chromatography–olfactometry (GC–O) was carried out to select the important odorants for subsequent comprehensive gas chromatography/time of flightmass spectrometry (GC × GC–ToFMS) analysis. By GC–O fifteen odorants were identified. For the quantification of volatile compounds, headspace solid phasemicroextraction (SPME) techniquewas optimized. Under optimized conditions, 22 volatile compounds were quantified in all samples. Trans-2-hexenal was the most abundant compound. A discriminant analysis (DA) was used to discriminate among olive oil samples obtained from olives of the two cultivars with different harvest time/ripening stages. Concerning the harvesting time and cultivar, nine volatiles showed to have discriminant power among samples, namely heptanal, trans-2-hexenal, 1-octen-1-ol, nonanal, 2,3-butanedione, ethyl-2-methylbutyrate, hexanal, cis-3-hexenylacetate and 3-methylbuthylacetate